2008
DOI: 10.1021/jp077402e
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Non-Condon Effect as the Origin of the Quantum Beat Observed in the Time-Resolved Absorption Signal from Excited-State cis-Stilbene

Abstract: We carried out wavelength-dispersed time-resolved absorption measurements of cis-stilbene to investigate the mechanism of the appearance of the approximately 220 cm-1 oscillation, which has been assigned to the nuclear wavepacket motion of the S1 state. The observed oscillatory pattern showed almost same amplitude and phase across the absorption peak at 645 nm, which indicates that the modulation of the transition intensity gives rise to the quantum beat. We also carried out a semiquantitative numerical simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…[10][11][12][13] In the meanwhile, however, the non-Condon vibronic coupling is also proposed to enhance the quantum coherence in many organic and biological molecular systems. [14][15][16] To obtain a better understanding of the origin of quantum coherence in EET dynamics, the interplay of the Condon and non-Condon vibronic coupling effects deserves more theoretical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In the meanwhile, however, the non-Condon vibronic coupling is also proposed to enhance the quantum coherence in many organic and biological molecular systems. [14][15][16] To obtain a better understanding of the origin of quantum coherence in EET dynamics, the interplay of the Condon and non-Condon vibronic coupling effects deserves more theoretical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The DEOM construction starts with an exponential expansion of correlation function satisfying Eq. (11) as…”
Section: B Bath Correlationsmentioning
confidence: 99%
“…[6][7][8][9] It is found that the non-Condon vibronic coupling would affect this quantum coherence enhancement. [10][11][12] Spectroscopic studies on EET systems have been widely carried out to reveal the structures and underlying dynamic processes in these systems. [13][14][15][16][17][18] In reality, EET constitutes an open quantum process where intramolecular nuclear vibrations and the surrounding solvent would coordinatively play important roles.…”
Section: Introductionmentioning
confidence: 99%
“…the description of ultrafast spectroscopic measurements. 55,56 A higher-order term is introduced to the dipole moment as…”
Section: B Nonlinear Couplingmentioning
confidence: 99%